Construction of Knowledge and Learning Experience to Build Digital Literacy in Marginal Communities - Rivo Nugroho; Sjafiatul Mardliyah; Heru Siswanto; Monica Widyaswari; Teguh Dewangga (Journal of Nonformal Education, 2024)
Digital literacy is a construction of knowledge and experience for suburban communities in using social media, with various ways used by the community to appreciate the presence of digital technology to help people work online, as well as appreciation from marginal communities along with the development of digital literacy into a construction of knowledge and experiential study. This study employs a qualitative approach with a case study method, focusing on 10 informants who are members of the Mulung Village community, active members of a youth organization, and community facilitators. The research results show that the construction of knowledge and learning experiences in building digital literacy for marginalized communities in marginal communities, which is manifest in community appreciation for the presence of digital technology, which provides convenience, new insights, and benefits as informal learning within the family, acting a mass communication tool, as a forum for the younger generation to discuss, social interaction in cyberspace, and generating consumer behavior in society, as well as an exploration of the younger generation’s skills and knowledge in using social media. In conclusion, digital literacy can foster community connection among marginalized communities through mass communication, independent learning experiences, and social media forums, fostering tolerance and empathy, and fostering support for digitalization through a sense of empathy and community support. The study’s novelty lies in its in-depth exploration of the interplay between digital literacy, community engagement, and empowerment, particularly for marginalized groups. It demonstrates how digital literacy can foster a sense of belonging, tolerance, and empathy within the community, ultimately leading to a more inclusive and supportive environment for digitalization.